Efektivitas Ekstrak Kulit Pisang Kepok (Musa Paradisiaca L) Terhadap Candida albicans dan Streptococcus mutans Sebagai Pembersih Basis Akrilik Gigi Tiruan Lepasan - Desy Purnama Sari; Eni Rahmi; Ivony Fitria (Andalas Dental Journal, 2023)
Background: Banana peels are always thrown away because they are considered items that cannot be eaten or reused, but recent study prove that it contains effective ingredients that can be used as antibacterial and antifungal agent. Kepok banana peel (Musa paradisiaca L) can kill and inhibit certain types of bacteria, including Streptococcus mutans and Candida albicans. Objective: To analyze the effectiveness of banana peel extract (Musa paradisiaca L) as a denture cleanser on the removable denture acrylic plate. Methods: This is an experimental laboratory using 48 denture acrylic plates, size 10x10x2 mm. Kepok banana peels were extracted by maceration technique to concentration of 25%, 50% and 75% and used aquadest as control group. Moreover, 24 acrylic plates in each group that cultured by Candida albicans ATCC (American Type Culture Collection) 10231 dan dan Streptococcus mutans ATCC 25175 were soaked into four solutions (6 plates in each treatment), then total colony was counted by the Total Plate Count (TPC) method. The data was analyzed by computerized by one-way Annova with posttest only-control group design. Results: Reducing the amount of Candida albicans was most effective at a concentration of 75% with an average of 62.33 ± 25.91 (p=0.000), meanwhile the 50% concentration was the most effective on Streptococcus mutans with an average of 0.43 ± 0.41 (p=0.035). Conclusion: Kepok banana peel extract had an good effect on reducing the number of Candida albicans and Streptococcus mutans colonies on the removable denture acrylic plates.